Metal induced charge transfer doping in graphene-ruthenium hybrid interconnects. (15th October 2021) - Achra, Swati; Wu, Xiangyu; Trepalin, Vadim; Nuytten, Thomas; Ludwig, Jonathan; Afanas'ev, Valeri; Brems, Steven; Sorée, Bart; Tokei, Zsolt; Heyns, Marc; Asselberghs, Inge
Abstract: To enable graphene-integrated interconnects in modern VLSI circuits, a major roadblock is developing an efficient Back End of Line (BEOL) compatible doping technique. In this paper, we demonstrate metal-induced doping of graphene in graphene-ruthenium hybrid structures. We study doping by systematically performing different material characterization techniques – Internal Photoemission Spectroscopy (IPE), Raman Spectroscopy and Kelvin Probe Force Microscopy (KPFM) to gain a deeper understanding on the charge transfer at the graphene-Ru interface. In IPE, we measure the relative band alignment of graphene and Ru, the interface potential barrier and effective work function of 4.9eV. With Raman spectral mapping, we report p-type doping in single layer graphene on Ru film with carrier density 1.9E13cm −2 . And with KPFM, Fermi-level shift of ∼420 meV (wrt intrinsic graphene) is observed implying downward shift of Fermi level in the graphene valence band. Electrically, graphene capping results in ∼19 % drop in sheet resistance of Ru accompanied by significant decrease in contact resistance. Moreover, the temperature coefficient of resistance reduces after graphene capping indicating better response to thermal fluctuations. By performing an extensive study using different material and electrical techniques, our results provide a viable and practical basis for integrating graphene as a conductor in advanced interconnects. Graphical abstract: Image 1